Plant-Based Antioxidant Extracts and Compounds in the Management of Oral Cancer - Suraj Prakash; Radha; Manoj Kumar; Neeraj Kumari; Mamta Thakur; Sonia Rathour; Ashok Pundir; Abhishek Kumar Sharma; Sneh Punia Bangar; Sangram Dhumal; Surinder Singh; Anitha Thiyagarajan; et al. (MDPI AG, 2021)
Oral cancer continues to be a leading cause of death worldwide, and its prevalence is particularly high in developing countries, where people chew tobacco and betel nut on a regular basis. Radiation-, chemo-, targeted-, immuno-, and hormone-based therapies along with surgery are commonly used as part of a treatment plan. However, these treatments frequently result in various unwanted short- to long-term side effects. As a result, there is an urgent need to develop treatment options for oral cancer that have little or no adverse effects. Numerous bioactive compounds derived from various plants have recently attracted attention as therapeutic options for cancer treatment. Antioxidants found in medicinal plants, such as vitamins E, C, and A, reduce damage to the mucosa by neutralizing free radicals found in various oral mucosal lesions. Phytochemicals found in medicinal plants have the potential to modulate cellular signalling pathways that alter the cellular defence mechanisms to protect normal cells from reactive oxygen species (ROS) and induce apoptosis in cancer cells. This review aims to provide a comprehensive overview of various medicinal plants and phytoconstituents that have shown the potential to be used as oral cancer therapeutics.